Hubungan Konflik Tokoh Dengan Politik Dan Teori Konspirasi Dalam Film “Mencuri Raden Saleh” - Nur Fadilah, Malika; Sodiq, Syamsul (CV. SINAR HOWUHOWU, 2025)
The main problem raised in this study is about the relationship between the character's conflict with politics and conspiracy theories in the film